The effect of education costs and location on the decision of parents to enroll children in an integrated islamic elementary school through a reference group in tangerang and jakarta selatan - Rahayu Lestari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Currently, many parents are more careful in choosing a school for their child. Of course, this is understandable, considering their children's future success. In Indonesia, of course, there are many schools, ranging from regular schools to several, that offer several advantages, from facilities to excellent programs to extracurriculars. One of the options for parents today is to send their children to religious-based educational institutions. This study aims to prove the effect of education costs and the location of parents' decisions to send their children through referral groups in Tangerang and South Jakarta. This research uses quantitative research methods. Sampling was based on a purposive sampling method of 100 respondents in Tangerang and South Jakarta using proportional random sampling in Tangerang and South Jakarta. The analytical method used is statistical-partial least square using SEM Lisrel 8.70 analysis software tools. The results of this study show that the cost of education significantly affects the reference group. The location has an effect but is not significant to the reference group. The reference group has an effect, but not significantly, on the decision to send their children to school.